Hammerhead ribozymes going viral. Issue 1 (December 2016) - Hammann, Christian
Abstract An association between hammerhead ribozymes and non-autonomous, long terminal repeat retrotransposons is uncovered in plants, shedding light on the biological function of genomically encoded ribozymes.